Usaha Pengolahan Dan Pemasaran Ikan Salai Patin (Kasus Di Desa Penyasawan Kecamatan Kampar, Riau) - Ramli, M. (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
The study aims to determine the state of smoked catfish processing business,with particular regard to production and marketing systems. Research conducted inthe Penyasawan village Kampar District, Riau. There are nine smoked catfishprocessors, the processor uses all of the raw materials and other supporting materialsin the same amount, relative to the same production capacity in a single productioncycle, which differ only in frequency processing. Of the nine processors, twoprocessors to produce 1 time / week, six processors to produce 2 times / week, and aprocessor to produce 3 times / week. 500 kg of raw materials has resulted in 150 kgof smoked catfish, with production costs Rp 7.060,000, - or Rp 47,066.66 per kg ofsmoked atcfish. Smokedcatfish is sold at Rp 55,000 per kg. Smoked catfish sold bydirect marketing by a processing system to the nearest markets around the county,and the system of indirect marketing (distribution channels) through traders tomarkets outside the district. The main problem is the problem faced by processingabsorption smoked catfish market is still low and the credit ratings of traders.